Use of a Clinical Reasoning Activity to Assist with Interprofessional Communication. (3rd April 2023) - Cunningham, Shala; Cunningham, Cynthia; Foote, Lisa
Abstract: Aims: The purpose of this pilot study was to explore differences in clinical diagnoses, clinical assessment data needed to support the diagnoses, and potential interventions using a case-based clinical learning activity involving a think-aloud process for nursing and physical therapy students. Methods: This study utilized a sample of convenience of 40 physical therapy students and 60 nursing students from southwest Virginia. To assist the students with communication of their perspectives on patient care through the use of the think-aloud process, a clinical reasoning activity was instituted. Results: By considering each other's perspectives on care priorities, the students were able to collaborate in developing a care plan that holistically addressed the health conditions of a geriatric patient in the home health setting. Conclusions: Providing healthcare students insight into the distinguishing perceptions of patient care associated with each profession may improve future communication, coordination, and collaboration to provide quality patient care.